Selected aspects of infectious disease evolution in the modern world - V. V. Maleyev (Кубанский научный медицинский вестник, 2020)
The article presents current views on the evolution of infectious processes and the role of infectious diseases in global healthcare. The reversion of the main components of epidemic processes leads to an atypical course of many infectious diseases and to the emergence of new transmission pathways. Urbanisation, global climate change, agroindustrial boost, migration waves and other factors provoked a cross-border expansion of many wild focal infections across countries and continents. The high morbidity and mortality of infectious diseases are determined by novel and “resurrecting” infections. The possibility of appearing both epidemic and pandemic outbreaks of emergent infections is as relevant as ever.In this context, the impact of modern scientiﬁc achievements on environmental microbiotic associations and human microbiome, as well as safety of medical technologies, is of paramount importance.Despite current progress in the drug therapy of infectious diseases, a serious emerging challenge is ampliﬁed antimicrobial resistance and drug interference.